2019
DOI: 10.1088/1674-1056/ab4176
|View full text |Cite
|
Sign up to set email alerts
|

Helicity of harmonic generation and attosecond polarization with bichromatic circularly polarized laser fields*

Abstract: We theoretically investigate the high-order harmonic generation (HHG) of helium atom driven by bichromatic counter-rotating circularly polarized laser fields. By changing the intensity ratio of the two driving laser fields, the spectral chirality of the HHG can be controlled. As the intensity ratio increases, the spectral chirality will change from positive- to negative-value around a large intensity ratio of the two driving fields when the total laser intensity keeps unchanged. However, the sign of the spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…The strong-field physics is a hot topic in recent years, and interaction of laser with atoms or molecules can produce different physical phenomena, including high order harmonic generation (HHG), [1][2][3] strong-field ionization, and nonsequential double ionization (NSDI). [4] The electron processes of molecular reaction dynamics are investigated with the rapid advances of ultrashort and ultrafast intense laser technology [5][6][7] in the attosecond time regime (1 as = 10 −18 s) and sub-nanometer dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The strong-field physics is a hot topic in recent years, and interaction of laser with atoms or molecules can produce different physical phenomena, including high order harmonic generation (HHG), [1][2][3] strong-field ionization, and nonsequential double ionization (NSDI). [4] The electron processes of molecular reaction dynamics are investigated with the rapid advances of ultrashort and ultrafast intense laser technology [5][6][7] in the attosecond time regime (1 as = 10 −18 s) and sub-nanometer dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The ultrashort attosecond pulses can also induce electron charge migration, thus offering the possibility for probing the molecular structure and imaging the molecular reactions. [6][7][8] In the research, a variety of pulses and their combinations have been used to explore electron dynamics, including the high-order harmonic generation (HHG), [9][10][11][12][13][14] nonsequential double ionization (NSDI), [15][16][17][18] and the photoelectron momentum distribution (PMD). [19][20][21][22][23] Recently it was found that single ionization of atom by two oppositely circularly polarized, time-delayed attosecond pulses produce vortex patterns in PMDs, [24][25][26][27] which are sensitive to the time delay between the pulses, their handedness, and their relative phase.…”
Section: Introductionmentioning
confidence: 99%
“…When an atom is irradiated by such an intense ultrashort laser pulse, the ultra-wide-band (from ultraviolet to x-ray) coherent high-order harmonic generation (HHG) can be carried out. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] HHG has been applied in the attosecond science [19][20][21] and nonlinear optics in the XUV region. [22] The harmonic spectrum from atoms in the linearly polarized laser pulse presents typical characteristics: as the harmonic order increases, the intensity of the first few order harmonics drops rapidly, and then a so-called "plateau" appears, the harmonic intensity which changes little, and there is a cut-off (beyond this energy the harmonic intensity decreases rapidly) at the end of the plateau.…”
Section: Introductionmentioning
confidence: 99%